Anacroneuria (Plecoptera: Perlidae) from Central Brazil: new species, new geographic records, and taxonomic notes - Miguel, Marina [UNESP]; Almeida, Lucas Henrique de [UNESP]; Novaes, Marcos Carneiro; Bispo, Pitagoras da Conceicao [UNESP] (Magnolia Press, 2022)
In the present study, adult specimens ofAnacroneuria collected in streams were studied in order to understand the diversity of the genus in Central Brazil. Herein, a new species (A. froehlichi n. sp.) is described, new geographic occurrences are recorded (A. amargosa Righi-Cavallaro & Froehlich, 2013; A. mineira Novaes & Bispo, 2014; A. minuta Klap??lek, 1922; A. ofaye Froehlich, 2007; A. payagua Froehlich, 2007; A. singela Duarte & Lecci, 2016; and A. singularis Righi-Cavallaro & Lecci, 2010), and taxonomic comments are made. Additionally, photographs of the paratypes of A. dourada Jewett, 1960 and A. galba Jewett, 1960 are presented. A total of 16 species ofAnacroneuria are now recorded in Central Brazil.
Keywords: Aquatic insects; Stoneflies; Streams; Cerrado; Neotropical